Skills Sets for Workforce in the 4th Industrial Revolution: Expectation from Authorities and Industrial Players - Saari, Aizuddin; Rasul, Mohamad Sattar; Mohamad Yasin, Ruhizan; Abdul Rauf, Rose Amnah; Mohamed Ashari, Zool Hilmi; Pranita, Diaz (Journal of Technical Education and Training, 2021)
Klaus Schwab, founder and executive chairman of the World Economic Forum announced the arrival of a new revolution, the Fourth Industrial Revolution (4IR), characterized by a combination of technology that changes the line between fields and is driven by three megatrends of digital, physical systems and biological along with ways that will change peopleâ€™s lives and the job market in the future.The arrival of the 4IR needs a further action on identifying industry trends, job demands and possibilities that may arise in parallel with this revolution especially to strengthening potential for skills development inline with 4IR. The skill sets required in both existing and new occupations will change and transform on how people work. The aim of the article is, to understand, as well as between developed and emerging markets, the employment, skills and education concerns of individuals. A qualitative research design with a focus group was used to collect data for this study. The focus group method entails focus group discussions on the aspect of strengthening human potential for skills development inline with 4IR, involving stakeholders members from the competence body which is Department of Skills Development (DSD) Malaysia, industry players from Industry Lead Body (ILB) appointed by DSD of various industry and an academician from the different TVET institutions.The findings showed four strategic aspect that can be used as a guideline to develop the skills set for 4IR which are empowering digital skills, proficient in using high impact technology, entrepreneurial mindset and lastly skilled workers with a combination of technical skills and soft skills.